SARS-CoV-2 surveillance and testing: results of a survey from the Network of University Hospitals (NUM), B-FAST - Heinemann, Stephanie; Bludau, Anna; Kaba, Hani; Knolle, Percy; Grundmann, Hajo; Scheithauer, Simone (German Medical Science GMS Publishing House, 2021)
Background: The B-FAST project of the National University Network (NUM) examines and records applied surveillance strategies implemented in hospitals i.a., to protect patients and employees from infection.Methods: Infection control physicians in German university hospitals (UK), as well as non-university hospitals (NUK; Bavaria, Lower Saxony) were surveyed in March 2021 regarding SARS-CoV-2 testing/surveillance strategies in a cross-sectional study using a standardized online questionnaire. The focus was on screening strategies taking into account the "test" methods used (case history, PCR, antigen, antibody test).Results: The response rate was 91.7% (33/36) in UK and 11.3%-32.2% in NUK. Almost all hospitals (95.0%) performed a symptom and exposure check and/or testing upon inpatient admission. Non-cause-related testing (screening) of health care workers in COVID wards was preferably done by PCR in UK (69.7% PCR; 12.1% antigen), while NUK (29.9% PCR; 49.3% antigen) used antigen testing more frequently. Regardless of the type of facility, about half of the respondents rated the benefit of screening higher than the effort (patients: 49%; employees: 45%).Conclusion: Testing/surveillance strategies find a high level of acceptance at German hospitals and are generally carried out in accordance with the national testing strategy with differences depending on the level of care.